Impact of globalization on the procurement of drugs for the treatment of high-cost diseases in Colombia (2013)
In Colombia, it has become a serious problem of social and economic, the procurement of drugs for the treatment of diseases of high cost, and in general for almost all drugs, which are determined by a number of factors that affect the price which we have: the regulations existing in the country which grants some privileges exaggerated to national and international drug companies that produce and market these medicinesthe little or almost no State control in the regulation of these prices, despite the fact that there are organizations and agencies for their control, such as the Ministry of health and the National Commission of prices of medicines and medical devices CNPMDM, the law 100 of 1993 which regulates health in Colombia and that has created a more mercantilist system than true social service of access to health in the country, the recovery in the price of medicines by the EPS, which is three to four times more expensive that has ordered the CNPMDM, which has diesmado the health budget, being this one recovery of its factors more determinants, coadministration of the health system in Colombia by the judicial branch, as it is the only mechanism that patients have through the action of guardianship for the drugs and treatments covered and not covered by the POS. Different treaties and commercial agreements signed by Colombia, to regulate the price of medicines in the country, the absolute failure the country starting with the Executive and the legislative authorities not to create a State policy that put at waist once for all national and multinational drug companies that produce and sell different types of drugs, since it is the same Government that to promoted and catapulted its decisions with freedom of prices, which started since 2003 lack or total desacatamiento by producers, marketers and distributors of the circulars of the CNPMDM, the total absence of the State to enforce the law, the competition between laboratories to create a free market, and commit as usual guarded control regime and the lack of large scale production of high quality generic drugs. This scene for nothing is alagador for Colombian people, which in the article 23 of the Congress-approved health reform and this for review at the Constitutional Court, it is said that it came to regulate the price of medicines, but does not say through that mechanism, long, from that authority and under the supervision and supervision of that entity's control, since although now this price is regulated by circulars of the CNPMDM the most recent the 004 2013 entered into force only until next year, but as seen these resolutions only are a salute to the flag since none of the committed to the production line marketing and distribution of medicinal products abide by it for nothing.